Raman and IR spectroscopy as a promising approach to rapid and non-destructive monitoring of chlorogenic acid in protein matrices - Vershinina, Yulia; Reshetnikova, Elizaveta; Lv, Shixian; Kolesnik, Irina; Kapitanova, Olesya; Veselova, Irina (Frontiers in Chemistry, 2025)
Sunflower meal, a by-product of the oil extraction process from sunflower seeds, has high-quality protein content. Its low production cost, near-absence of toxic substances, and close to “ideal” amino acid composition give it several advantages over other plant-based protein sources. However, at the moment, the use of sunflower meal in the food industry is still limited. This is due to the high content of phenolic compounds (1-4 wt%), particularly chlorogenic acid. The oxidation products of these compounds easily bind to protein molecules, giving the final product a dark green color and bitter taste. Currently, there is a high demand for the development of methods for rapid monitoring of the content of phenolic compounds in plant materials without special processing at various stages of the technological process without preliminary sample preparation for analysis. In this study, we used non-destructive vibrational spectroscopy techniques–Raman and FTIR–to monitor the content of chlorogenic acid in the raw material. As a result, an approach for the determination of chlorogenic acid in sunflower meal using IR spectroscopy with limit of detection (LOD) 0.75 wt% has been proposed. Its content in the studied sample of sunflower meal was 5.6 wt%, which was confirmed by UV-spectroscopy and HPLC. The paper demonstrates the principal possibility of analyzing protein isolates using Raman scattering, with the LOD for chlorogenic acid content at 1 wt%.